2016
DOI: 10.1136/heartjnl-2016-310243
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes with type 2 myocardial infarction compared with non-ischaemic myocardial injury

Abstract: Patients with type 2 MI and NIMI were older, with higher proportion of women and more comorbidities than patients with type 1 MI. Absolute mortality and the adjusted risk for all-cause mortality in both groups were significantly higher than that of patients with type 1 MI (39.7%, HR: 1.41 95% CI 1.02 to 1.94, p=0.038 and 40.0%, HR: 1.54 95% CI 1.16 to 2.04, p=0.002, respectively). Patients with type 2 MI and NIMI tended to present more readmissions due to heart failure (16.5%, HR: 1.55 95% CI 0.87 to 2.76, p=0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 30 publications
6
50
1
6
Order By: Relevance
“…Firstly, raised cardiac troponin concentrations, particularly in patients not presenting with a typical history of cardiac pain, are often caused by myocardial injury or type 2 myocardial infarction 67. These conditions, which are secondary to ischaemia caused by increased oxygen demand or decreased supply rather than a plaque erosion,8910 are not well recognised when the troponin test is requested or the result interpreted.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, raised cardiac troponin concentrations, particularly in patients not presenting with a typical history of cardiac pain, are often caused by myocardial injury or type 2 myocardial infarction 67. These conditions, which are secondary to ischaemia caused by increased oxygen demand or decreased supply rather than a plaque erosion,8910 are not well recognised when the troponin test is requested or the result interpreted.…”
Section: Introductionmentioning
confidence: 99%
“…Both type 1 and type 2 MI can present as NSTEMI or STEMI, although NSTEMI is more common for both types . Most NSTEMI pathophysiologically are consistent with type 1 MI, but the relative proportions of type 1 NSTEMI and type 2 NSTEMI vary between clinical settings …”
Section: Discussionmentioning
confidence: 99%
“…Underlying conditions that may predispose individuals to oxygen supply‐demand imbalances, and thus type 2 MI, include hypotension, sepsis, anemia, tachyarrhythmia, respiratory failure, and hypertension . In addition to CV differences, a number of studies have shown that patients who have a type 2 MI are usually older, more often women, and more likely to have a history of comorbidities such as heart failure, arrhythmias, chronic obstructive pulmonary disease, or renal impairment …”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…hs-cTn assays are less specific than contemporary assays for MI, as more patients with non-ACS conditions have hs-cTn elevations that are missed with the contemporary assay [22]. While patients with hs-cTn elevations have increased downstream mortality, regardless of cause [23, 24], the optimal testing and management strategies for non-ACS patients with hs-cTn elevations are unclear. Therefore, some have been concerned about the impact of integrating hs-cTn assays into an ADP, such as the HEART Pathway, which has previously demonstrated a sensitivity >99% for 30-day MACE using serial contemporary cTn measures.…”
Section: Discussionmentioning
confidence: 99%